Respon Pertumbuhan Tiga Varietas Selada (Lactuca sativa L.) terhadap Konsentrasi Nutrisi AB Mix Secara Hidroponik - Agung Wibowo , Ridlo; Furoidah , Nanik (JURNAL AGROPLANT, 2021)
Alternative ways to meet the needs of vegetables as their daily nutritional intake for the body, one of the leaf vegetables like lettuce are rich in vitamins, minerals, and other nutrients. Public awareness of the importance of eating vegetables is increasing lately, ironically, the availability of agricultural land decreases due to the conversion of agricultural land. One effort that can be done is by vegetable hydroponic farming. The research objective was to determine the best response of varieties of lettuce on levels of nutrient concentrations (AB mix). The research was conducted in the village of Jember Kidul, District Kaliwates Jember in altitude ± 100 m above sea level, in April to June 2016. The study was conducted using a randomized block design (CRD) consisting of two factors: the first factor is the concentration of the nutrient treatments AB mix (K) consisting of 500 ppm (K1), 550 ppm (K2), 600 ppm (K3). The second factor is the treatment of a wide variety of green lettuce is lettuce green Maat (V1), green lettuce green olivia (V2), red lettuce lolo rosa (V3). The results showed matt green lettuce varieties (V1) has the best growth response and significantly different on all parameters except observations observation root length. Treatment nutrient concentrations AB Mix real effect only on the parameter number of leaves and the fresh weight of the total that is best at a concentration of 600 ppm (K3), but no significant effect on observations of plant height, root length and dry weight. Interaction between wide varieties of lettuce and nutrition konstrasi AB Mix all parameters showed no significant observations.